PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI FLUIDA - Asma Yani; Elisa Kasli; Saminan Saminan (Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2017)
This study aims to know the result of student learning, teacher and student activity, teacher skill in managing learning, and student's response to the use of STAD (Student Team Achievement Division) Cooperative Learning Model in learning process. This type of research is Classroom Action Research Using a quantitative method. The subjects of this study are students of X-IPA 1 SMA Negeri 1 Seunagan academic year 2016/2017 which amounted to 27 students, 3 male students and 24 female students. This research data obtained from the results of pre-test and post-test students, then processed using statistical methods and explained again using words. The result of the research shows that,) the increase of teacher and student activity during the learning process, there is improvement of teacher skill in managing learning from good category to excellent  overall percentage of overall mastery increase from cycle 1 to cycle 3. students' responses tend to be positive where 94% of students express happy about learning by using STAD type cooperative learning. Based on this research, it can be concluded that the application of cooperative learning model type STAD (Student Team Achievement Division) can improve student physics learning outcomes on the subject of Static Fluid class X-IPA 1 SMA Negeri 1 Seunagan.